A comparative evaluation of three dimensional accuracy of different types of interocclusal recording materials - an in vitro study - Dwivedi, Aparna; Maru, Kavita; Sharma, Aakash (Medicine and Pharmacy Reports, 2020)
Introduction. The interocclusal registration materials record the occlusal relationship between the natural and /or artificial teeth for planning an occlusal rehabilitation in removable and fixed partial dentures. Aim and objectives. The aim of this in vitro study was to evaluate and compare the accuracy and the three dimensional stability offered by three different types of interocclusal recording materials at storage time intervals of 1 hour and 24 hours. Methods. Three commercially available interocclusal recording materials were used - Group I - Polyether bite registration paste (Ramitec), Group II- Polyvinylsiloxane bite registration material (Imprint), Group III- Bite registration wax (Maarc).The test was carried out using an epoxy resin model. A total of 30 samples were made with each group consisting of ten samples. Three dimensional measurements were carried out by using 3D-Coordinate measuring machine (CMM) at time intervals of 0-1 hour and 0-24 hours in X, Y and Z- axis. Results. Twelve readings were obtained for three axes (4 readings for each sample at 1 axis) and the averages of these four values were noted for a particular axis (X/Y/Z). Statistical analysis was performed using analysis of variance (ANOVA) for comparison among the groups and then Tukey’s honestly significant difference (HSD) tests was performed for comparison among groups at the 0.05 level of significance. Conclusion. Polyvinylsiloxane was dimensionally the most stable material followed by polyether and finally bite registration wax. Dimensional accuracy and stability is influenced by both “material” and “time” factors.